Challenges of access to medicine and the responsibility of pharmaceutical companies: a legal perspective. Issue 1 (December 2016) - Ahmadiani, Saeed; Nikfar, Shekoufeh
Abstract The right to health as a basic human right- and access to medicine as a part of it- have been a matter of attention for several decades. Also the responsibilities of different parties- particularly pharmaceutical companies- in realization of this right has been emphasized by World Health Organization. This is while many companies find no incentive for research and development of medicines related to rare diseases. Also some legal structures such as "patent agreements" clearly cause huge difficulties for access to medicine in many countries. High prices of brand medicine and no legal production of generics can increase the catastrophic costs- as well as morbidity-mortality of medication in lower income countries. Here we evidently review the current challenges in access to medicine and critically assess its legal roots. How societies/governors can make the pharmaceutical companies responsible is also discussed to have a look on possible future and actions that policy makers- in local or global level- can take. Graphical Abstract Challenges of access to medicine and the responsibility of pharmaceutical companies: a legal perspective.